Benetzungsverhalten von Kohlenstoffnanoröhren. Issue 3 (6th February 2014) - Dresel, Alexander; Teipel, Ulrich; Teipel, Ulrich; Weber, Alfred
<x xml:space="preserve">Abstract</x> Carbon Nanotubes are particles with graphit‐like shells and diameters in the nanorange. Since they are often dispersed in fluids, the particle‐fluid interactions are important product properties. However, the characterization of the wetting behavior of disperse systems can be problematic because methods for direct contact angle measurements cannot be easily applied. This work presents the investigation of the wetting behavior of non‐modified and functionalized, multi‐walled carbon nanotubes with the liquid penetration method regarding Washburn.